Analysis of new mathematical model for rabies through wavelet method - Yeshwanth, R.; Kumbinarasaiah, S.; Dhawan, Sharanjeet (Frontiers in Applied Mathematics and Statistics, 2025)
Rabies is a fatal zoonotic disease caused by a virus, primarily spread through bites or saliva. Dogs are the main source of human infections worldwide. This article introduces a new mathematical model using fractional differential equations to analyze rabies transmission dynamics. The model consists of four compartments: susceptible and infected populations of both humans and animals, forming a system of fractional differential equations (SOFDEs). The modified Hermite wavelet collocation method (HWCM) is used to solve these equations by converting them into a non-linear algebraic system. Newton-Raphson's approach determines the unknown Hermite coefficients, and the results are compared with ND Solver and RK4 methods. Visual and numerical analysis confirms the proposed method's superior accuracy and effectiveness.